Behavior in the presence of dysplasia and carcinoma in situ of the cervix - Zuckermann, Conrado (2015)
The author revises the hypothesis, nomenclature and problems of the dysplasia and carcinoma in situ of the cervix as presented by different authors and his personal experience form 1958-67 consisting in 428 cases of dysplasia and 236 carcinoma in situ. Remarking that both entities do not mean emergencies, the author establishes his preference by the conservative treatment of the dysplasia and the surgical approach of the carcinoma in situ with conization, or total hysterectomy with extirpation of the upper part of the vagina